Mechanical Characteristic Analysis of Buried Drainage Pipes after Polymer Grouting Trenchless Rehabilitation - Jian-guo Xu; Zhi-hao Chen; Ren Wang (Advances in Civil Engineering)
The application of polymer grouting in underground pipeline rehabilitation is increasing gradually. The leakage and subsidence of buried pipelines could be repaired by polymer grouting technology. In order to analyse the calculation theory of the pipeline repairing process, the Winkler model and the Vlazov model of the pipe-soil-polymer interaction based on the elastoplastic theory are established, the calculation formulas of the pipe-soil interaction under polymer grouting are derived, and the MATLAB calculation program based on the transfer matrix method is compiled. Then the calculated values are compared with the pipeline experimental values, and the influence of different factors on the internal force and deformation of the polymer-repaired pipeline under different work conditions is discussed. The results show that the values and trends of the pipe deformation and circumferential bending moment calculated by the models are consistent with the experimental results, and the results obtained by the Vlazov model are closer to the experimental values. In addition, the void at the bottom of the pipeline has a large impact on the mechanical properties of the pipeline. However, polymer grouting can repair disengaged pipelines effectively and restore their mechanical properties. The proposed methods and calculation results are valuable for pipeline polymer repairing analysis and pipeline void repairing design.